Perspectives on Jazz Synthesizer Improvisation: Analyzing Recorded Solos by Jan Hammer, Joe Zawinul, George Duke, Chick Corea, and Michael Brecker - Mertanen, Visa-Pekka Oskari (Taideyliopiston Sibelius-Akatemia, 2025)
This thesis studies different perspectives on jazz synthesizer improvisation by examining five recorded solos: “Celestial Terrestrial Commuters” [Birds of Fire], “Black Market [8:30] “Brazilian Sugar” [Brazilian Love Affair] “Got A Match?” [Chick Corea Electric Band] and “Gossip” [Michael Brecker Band Live] as well as published interviews of their original performers: Jan Hammer (1948-), Joe Zawinul (1932-2007), George Duke (1946-2013), Chick Corea (1941-2021) and Michael Brecker (1949-2007). The primary research method employed is artistic practice-based, which consists of self-learning by aural imitation and music theory analysis. In the research process, synthesizer solos from the original recordings were imitated, transcribed, and analyzed. The source material comprises four doctoral concerts, audio recordings, videos, books, scholarly articles, magazine articles, and internet sources. The studied solos and accompanying parts were transcribed by the author and chosen from the repertoire of the doctoral concerts in which the author performed original compositions and music frequently performed by the studied musicians. The analysis brings out the contextual background, synthesizer setups, and sound design. The transcription analysis focuses on rhythmic and melodic-harmonic phenomena such as scale choices, note choices, patterns, nuancing, timbral qualities, form, and tension control. At the end of each section covering a solo, there is a summary of the most essential qualities of that solo, along with an imitation video by the author. The findings show that the critical elements in jazz synthesizer soloing are mastering the improvisatory languages of the jazz tradition and adjusting the playing style to each sound’s acoustic character. The studied solos demonstrate different ways of nuancing the notes with continuous controllers and manipulating the sound's timbral qualities to keep the synthesizer sound expressive and exciting. A comparison chart of the studied musician’s personal data, song information, improvisational concepts, synthesizer setups, solo sound characters and realtime controllers found in the five solos is presented at the end.
Keywords: Hammer, Jan.; Zawinul, Joe.; Duke, George.; Corea, Chick.; Brecker, Michael.; jazz; improvisointi; syntetisaattori; musiikki; soolo-osuudet; musiikkianalyysi; taiteellinen tutkimus; muusikot; fuusiomusiikki; MuTri